2021
DOI: 10.1038/s41594-021-00570-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for inhibition of the SARS-CoV-2 RNA polymerase by suramin

Abstract: evere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic of coronavirus disease 2019 (COVID-19), with over 84.66 million infections and 1.83 million deaths as reported on 3 January 2021 (refs. 1,2). SARS-CoV-2 is a positive-sense, single-stranded RNA virus. SARS-CoV-2 and several related beta-coronaviruses, including SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), are highly pathogenic. Infections can lead to severe acute respiratory syndrome, loss of lung … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
157
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(163 citation statements)
references
References 36 publications
6
157
0
Order By: Relevance
“…The complexes were not changed and were taken for computations as they are. RdRp complexes with favipiravir-RTP (7AAP und 7CTT) and with suramin (7D4F) [ 28 ] were selected and analyzed ( Figure 1 ). In 7AAP and 7CTT complexes, the favipiravir-RTP ligand has different conformations.…”
Section: Methodsmentioning
confidence: 99%
“…The complexes were not changed and were taken for computations as they are. RdRp complexes with favipiravir-RTP (7AAP und 7CTT) and with suramin (7D4F) [ 28 ] were selected and analyzed ( Figure 1 ). In 7AAP and 7CTT complexes, the favipiravir-RTP ligand has different conformations.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike earlier expectations, remdesivir appeared to have little, or no, effect on hospitalized COVID-19 patients in terms of overall mortality, initiation of ventilation and duration of hospital stay 124 , 125 . Yin et al 126 have reported that suramin, a 100-year-old drug, and its derivatives are at least 20-fold more potent than remdesivir in inhibiting SARS-CoV-2 infection by targeting RdRp. The crystal structure of RdRp in complex with suramin has revealed two binding sites in RdRp ( Fig.…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Viral Proteinsmentioning
confidence: 99%
“…5 C). As a non-nucleotide inhibitor, suramin could ultimately aid in structure-based drug development for COVID-19 126 .…”
Section: Small-molecule Sars-cov-2 Inhibitors Targeting Viral Proteinsmentioning
confidence: 99%
“…Additionally, in order to serve as a marker of replicating virus, sgRNA is expected to show a rapid decline after transcriptional inhibition due to ribonuclease degradation, in contrast to gRNA, which may be protected from degradation by viral capsids and therefore persist more durably (16). Therefore, we hypothesized that, upon treatment with SARS-CoV-2 RNA-dependent RNA polymerase inhibitors (17, 18, 19) in cell lines infected with SARS-CoV-2, we should observe a rapid decline of sgRNA after viral death when compared with gRNA.…”
Section: Introductionmentioning
confidence: 99%